Effect of the Essential Oil of Zanthoxylum Armatum DC. (Rutaceae) Against Aphid (Aphis Citricidus) (SAARC Journal of Agriculture, 2023)
Aphids have been considered as a major pest of cultivated crops and invade a wide range of vegetables, cereals, and fruits. Use of synthetic chemical insecticides are the common aphid management practices in the world. The use of chemical insecticides/pesticides raises many concerns associated with the environment, biodiversity and human health. Therefore, the use of natural products such as essential oils have been tested extensively to assess their insecticidal and repellent activity. In this study different concentrations (0.1%, 0.2%, 0.3%, 0.4% and 0.5%) of essential oil (EO) from seeds of Zanthoxylum armatum were tested for their insecticidal and repellent activity for aphids using direct toxicity and repellency method. Results revealed that mortality and repellency were concentrations and exposure time dependent. Mean mortality percentage increased with the increasing concentration and exposure time. 100% mortality was observed in 0.5% concentration after 48 hrs exposure time. However, repellent activity increases with the increasing concentration and decreases with the increasing exposure time. The maximum repellence percentage (96.29%) was achieved in 0.5% oil concentration after 24 hrs of exposure time. Gas Chromatography - Mass Spectrometry (GC-MS) analysis of the essential oil revealed the presence of three major compounds such as Eucalyptol (46.47%), Methyl Cis-Cinnamate (11.13%), and D-Limonene (7.10%) reported as insecticidal activity.SAARC J. Agric., 21(2): 183-194 (2023)